2019
DOI: 10.3389/fmicb.2019.01153
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Basis of Symbiosis: A Heterologous Partner Fails to Duplicate Homologous Colonization in a Novel Cnidarian– Symbiodiniaceae Mutualism

Abstract: Reef corals and sea anemones form symbioses with unicellular symbiotic dinoflagellates. The molecular circumventions that underlie the successful intracellular colonization of hosts by symbionts are still largely unknown. We conducted proteomic analyses to determine molecular differences of Exaiptasia pallida anemones colonized by physiologically different symbiont species, in comparison with symbiont-free (aposymbiotic) anemones. We compared one homologous species, Symbiodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 86 publications
(114 reference statements)
3
25
0
Order By: Relevance
“…B. minutum density increased further over time, reaching a maximum of 127 ± 2 cells/mm 2 at 30 dpi. These results are congruent with our identification of B. minutum as the homologous symbiont in GBR anemones and are consistent with previous works showing that the homologous symbiont is the most efficient colonizer of other E. diaphana genotypes (Belda-Baillie et al, 2002;Xiang et al, 2013;Gabay et al, 2018Gabay et al, , 2019Parkinson et al, 2018;Medranos et al, 2019;Sproles et al, 2019). Such an affinity profile is not exclusive to anemones, as it has also been reported in several corals (Weis et al, 2001;Rodriguez-Lanetty et al, 2003, 2004Wolfowicz et al, 2016;Lin et al, 2019).…”
Section: Homologous Symbionts Are the Most Effective Colonizerssupporting
confidence: 93%
See 1 more Smart Citation
“…B. minutum density increased further over time, reaching a maximum of 127 ± 2 cells/mm 2 at 30 dpi. These results are congruent with our identification of B. minutum as the homologous symbiont in GBR anemones and are consistent with previous works showing that the homologous symbiont is the most efficient colonizer of other E. diaphana genotypes (Belda-Baillie et al, 2002;Xiang et al, 2013;Gabay et al, 2018Gabay et al, , 2019Parkinson et al, 2018;Medranos et al, 2019;Sproles et al, 2019). Such an affinity profile is not exclusive to anemones, as it has also been reported in several corals (Weis et al, 2001;Rodriguez-Lanetty et al, 2003, 2004Wolfowicz et al, 2016;Lin et al, 2019).…”
Section: Homologous Symbionts Are the Most Effective Colonizerssupporting
confidence: 93%
“…It is common for E. diaphana to have affinities for heterologous symbionts ( Table 1). For instance, anemone genotype CC7 exhibits high compatibility for the homologous algae of E. diaphana from other regions (Hambleton et al, 2014;Wolfowicz et al, 2016), and the genetic lines of anemones from both Atlantic and Indo-Pacific regions are able to establish symbiosis with members of the Durusdinium genus (Wolfowicz et al, 2016;Gabay et al, 2018;Medranos et al, 2019;Sproles et al, 2019). This matrix of compatibility/incompatibility between hosts and symbionts probably represents an underlying system of genetic match-ups that regulates which partnerships occur in any given region, but the underlying cellular mechanisms are completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas multiple investigations have queried the cnidarian host to compare conditions of symbiosis and aposymbiosis (e.g., Kuo, Chen, Lin, & Fang, 2004;Lehnert et al, 2014;Medrano, Merselis, Bellantuono, & Rodriguez-Lanetty, 2019;Oakley et al, 2016;Rodriguez-Lanetty, Phillips, & Weis, 2006), there has been limited inquiry into the changes which take place in Symbiodiniaceae when free-living dinoflagellates switch to an in hospite, endosymbiotic lifestyle. Previous work has included gel-based protein profiling of changes between in hospite and cultured Symbiodiniaceae (Pasaribu et al, 2015;Stochaj & Grossman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the expression levels of proteins related to antioxidant or heat stress phenotypes were roughly the same, while proteins involved in protein biosynthesis were highly expressed. Proteomics has also been used to compare the performance of different Symbiodiniaceae species [144,152]. Using LC-MS based proteomics, they compared proteomes of the model sea anemone Exaiptasia pallida colonized by different dinoflagellate symbiont ( B. minutum and Durusdinium trenchii ) [144].…”
Section: Omics Study On Dinoflagellatesmentioning
confidence: 99%
“…Results showed that in anemones containing D. trenchii (heterologous symbiont), Niemann-Pick C2 proteins, and glutamine synthetases were lowly expressed, while methionine-synthesizing betaine–homocysteine S-methyltransferases and proteins with predicted oxidative stress response functions were highly expressed when compared with anemones containing B. minutum (homologous symbiont). In another study, the researchers found that high-density symbiotic colonization required avoiding the immune responses of host cells, enhancing ammonium regulation, and inhibiting the phagocytosis of host cells after colonization [152]. iv) Proteins related to toxin biosynthesis were identified in A .…”
Section: Omics Study On Dinoflagellatesmentioning
confidence: 99%